Burned Area Comparisons Between Prescribed Burning Permits in Southeastern United States and Two Satellite‐Derived Products. Issue 9 (7th May 2018) - Huang, Ran; Zhang, Xiaoyang; Chan, Daniel; Kondragunta, Shobha; Russell, Armistead G.; Odman, M. Talat
Abstract: Prescribed burning (PB) is one of the most prominent sources of PM2.5 (particulate matter with an aerodynamic diameter less than 2.5 μm) in the southeastern United States. The PB emissions estimates may have significant uncertainty because they are based on the burned areas reported to the state agencies when burners apply for burn permits. When no permit records are available, satellite‐derived products could be used as a substitute tool to provide burned area data. In order to evaluate burned areas from satellite‐derived products, we conducted a comparison between PB permit records and two satellite‐derived products, Blended Polar Geo Biomass Burning Emissions Product and Global Fire Emissions Database, in Georgia and Florida. The comparison results indicate that both satellite‐derived products underestimate seriously the burned areas compared to permit record data. They can capture a cluster of fires better than isolated fires but may misinterpret those small fires together as one big fire. Overall, current satellite‐derived products have limitations in estimating the burned areas of small fires and still need improvements. Plain Language Summary: Prescribed burning is a preferred land management tool but also a prominent source of air pollution in the United States, and exposure to fire smoke is a growing health concern. Burned area is a direct input to the estimation of smoke emissions; therefore, it is critical to have accurate burned area data to be able to conduct reliable assessments of exposure to smoke. While some states like Florida and Georgia keep extensive prescribed burn records through permitting programs, other states may not even have a permitting system in place. In the absence of permit data, satellite products are the only recourse to obtaining burned area data. Previous studies have attempted to evaluate the uncertainty of burned areas by comparing different satellite products. In this study, we compared burned areas from prescribed burning permit records and two satellite products in Florida and Georgia during the 2015 and 2016 burning seasons. Burned areas in permit records are only preburn estimates, but a survey we conducted suggests that they are within 15% of the actual burned areas. Our comparison results show that current satellite products generally underestimate the burned areas of small fires and need several improvements for detection of prescribed burns. Key Points: Comparisons between permit record data sets and two satellite‐derived data sets show that satellite products underestimate the burned areas Satellite‐derived products can capture a cluster of fires better than isolated fires but may misinterpret them as one big fire Considering the deficiencies of satellite‐derived products, and the missing data caused by cloudy days, we trust the permit records more